2016
DOI: 10.1177/2158244016639112
|View full text |Cite
|
Sign up to set email alerts
|

Separating the Different Domains of Reading Intervention Programs

Abstract: Providing a child with reading difficulties with the appropriate reading intervention as early as possible is critical to prevent future academic failure. As reading is composed of several sub-components (phonology, orthography, fluency, comprehension), choosing the appropriate intervention may be confusing. Here, we attempt to provide an up-to-date review of different reading intervention programs and their outcomes that currently are available for children 4 to 16 years of age. We also introduce the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…They held that early training programs aiming at literacy awareness have showed lasting improvement as to working memory subscales. Other studies suggest effects by including components of executive functions training to initiate sessions of reading training (Horowitz‐Kraus & Finucane, ; Horowitz‐Kraus & Holland, ). Horowitz‐Kraus and Finucane concluded that multicomponent intervention programs with short executive functions “warm‐up” prior to literacy training seemed to be beneficial to reading.…”
Section: And Dyslexiamentioning
confidence: 99%
See 1 more Smart Citation
“…They held that early training programs aiming at literacy awareness have showed lasting improvement as to working memory subscales. Other studies suggest effects by including components of executive functions training to initiate sessions of reading training (Horowitz‐Kraus & Finucane, ; Horowitz‐Kraus & Holland, ). Horowitz‐Kraus and Finucane concluded that multicomponent intervention programs with short executive functions “warm‐up” prior to literacy training seemed to be beneficial to reading.…”
Section: And Dyslexiamentioning
confidence: 99%
“…They held that early training programs aiming at literacy awareness have showed lasting improvement as to working memory subscales. Other studies suggest effects by including components of executive functions training to initiate sessions of reading training (Horowitz-Kraus & Finucane, 2016;Horowitz-Kraus & Holland, 2015).…”
mentioning
confidence: 99%
“…As regards executive functions, many studies indicate that "language is the key to EF performance rather than vice versa" (Botting et al, p. 1, 2017, Lindstone, Meins, & Fernyhough, 2012. Additionally, the development of speech and executive functions appear to be crucial for literacy achievement during the school years (Horowitz-Kraus, Finucane, 2016). The present study compared executive functions and literacy skills of monolingual children diagnosed with SLI and their typically developing peers.…”
Section: Introductionmentioning
confidence: 84%
“…As previously stated, both a low level of EFs and SLI could be risk factors for school achievements (Blair & Razza 2007, Molfese et al, 2010, Jacobson, Williford & Pianta, 2011, Clark et al, 2013, Horowitz-Kraus, Finucane, 2016. Many studies indicate important links between executive functions, level of language development, and reading and writing acquisition (Molfese et al, 2010, Jacobson, Williford, & Pianta, 2011, Blair & Razza 2007, Horowitz-Kraus, Finucane, 2016. The development of literacy not only predicts school success but also predicts a high quality of life in adulthood (Beswick & Sloat, 2006;Kwieciński, 2002).…”
Section: Sli Executive Functions and Literacymentioning
confidence: 97%
See 1 more Smart Citation